Strategi Pemasaran Bank Muamalat Untuk Menarik Minat Masyarakat Dalam Memiliki Tabungan IB Hijrah Haji - Refiana Alfiah Widayanti; Amin Awal Amarudin (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2026)
This study aims to analyze the marketing strategies implemented by Bank Muamalat Jombang Branch in increasing public interest in the iB Hijrah Haji Savings product. Although various studies have discussed Islamic banking marketing strategies, studies on the effectiveness of the iB Hijrah Haji Savings marketing strategy at the branch office level, particularly at Bank Muamalat Jombang Branch. This study uses a qualitative approach with field research. Data were obtained through interviews, observations, and documentation of relationship managers and employees of Bank Muamalat Jombang Branch. Data analysis was conducted using the Miles and Huberman model which includes data reduction, data presentation, and drawing conclusions. The results show that Bank Muamalat Jombang Branch implements various marketing strategies, including establishing cooperation with related institutions, conducting personal approaches to potential customers, and utilizing social media as a promotional tool. Public interest in the iB Hijrah Haji Savings product is influenced by the ease of the registration process, recommendations from close friends, and a high level of trust in the bank. These strategies have been proven to increase the number of iB Hijrah Haji Savings account openings and provide customer satisfaction. The findings of this study provide practical implications for Bank Muamalat in designing more effective, adaptive, and digital-based marketing strategies to increase public interest in sharia hajj savings products.